Pendampingan Tata Kelola Sistem Informasi Berbasis Website Desa Senggreng Menuju Smart Village - Desinta Dwi Rapita; Sukma Ulandari; Sri Untari; Didik Sukriono; Azhar Ahmad Smaragdina; Ekaliya Priti Anggraeni (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The government has initiated the smart village concept as an effort to realize the ideals of a developed Indonesia. Senggreng Village is one of the villages that is trying to create a smart village. Through assistance with website-based village information system governance, it is hoped that it can facilitate the Senggreng Village government to produce a village system to improve digital-based public services with the principle of openness. Implementation of service is carried out by analyzing the stages of the community situation, identifying problems, determining goals, making problem-solving plans and agreements with partners, and determining activity agendas. The service activity agenda includes socialization and delivery of material, website creation training, mentoring, evaluation and follow-up. The results of the activities include the creation of website-based village information system governance, digitalization of information and services, utilization of village websites as a means of promoting and village tourism so that there is an opportunity to collaborate with external parties to develop Senggreng Village as a Smart Village.